Aerobic capacity and disease activity in children, adolescents and young adults with juvenile idiopathic arthritis (JIA) - van Pelt Philomine A; Takken Tim; van Brussel Marco; de Witte Mirjam; Kruize Aike A; Wulffraat Nico M (BMC, 2012)
Abstract Background As patients with juvenile idiopathic arthritis (JIA) progress into adulthood, long-term outcome is determined by disease activity, physical and psychosocial development. Decreased aerobic capacity may play a critical role in health-related outcomes in JIA, since it has been linked with cardiovascular morbidity and mortality in late adulthood. The objectives of the current study are to examine the aerobic capacity and its relation to parameters of disease activity in children, adolescents and young adults with JIA. Methods Sixty-three patients with JIA (aged 10-27 years) were cross sectional studied regarding their aerobic capacity and correlations were made to demographic, disease-related variables, and medication utilization. in a cross-sectional study group of 63 patients of all subtypes. Patients were divided in three age groups, 10-13 years; 14-17 years and 18-27 years. Results Reduced aerobic capacity is found in clinical remission as well as active disease in all subtypes and all age groups. Aerobic capacity is more impaired in active disease shown by DAS 28, JADAS 27, ESR and serum thrombocyte counts. Lower haemoglobin has a negative impact. Long-term used medication including methotrexate and corticosteroids didn't influence outcome. There is no association with current sports participation. Conclusion Reduced aerobic capacity is present in adolescents and young adults with JIA, both in active disease and in patients with remission. Measures of aerobic capacity may serve as important outcome measure in JIA.